2020
DOI: 10.24926/iip.v11i4.2937
|View full text |Cite
|
Sign up to set email alerts
|

Student Pharmacists’ Assessment of a Serious Game on Opioid Medication Safety

Abstract: Objective: To explore second- and third-year student pharmacists’ perspectives on the design and use of a digital game to teach opioid medication safety.  To explore the game-based learning approach to teach about appropriate drug use and pediatric education.   Innovation: The lead author developed MedSMA℞T: Adventures in PharmaCity, an educational video game focused on adolescent opioid safety.  Second- and third-year students in a Midwestern School of Pharmacy enrolled in an elective course focused on approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…56,88,[92][93][94] Thirty-five articles modified teaching methods with technology, often using technology to support changes to curriculum or teaching methods. Examples included the use of social media, 50 studentcreated digital resources, 95,96 serious games or escape rooms [97][98][99] and virtual and augmented reality. 64,65,100,101 With these examples, technologies were used in novel ways to allow students to learn more deeply or to extend learning beyond the traditionally possible.…”
Section: Samr Categorisationmentioning
confidence: 99%
“…56,88,[92][93][94] Thirty-five articles modified teaching methods with technology, often using technology to support changes to curriculum or teaching methods. Examples included the use of social media, 50 studentcreated digital resources, 95,96 serious games or escape rooms [97][98][99] and virtual and augmented reality. 64,65,100,101 With these examples, technologies were used in novel ways to allow students to learn more deeply or to extend learning beyond the traditionally possible.…”
Section: Samr Categorisationmentioning
confidence: 99%
“…A study conducted as part of a pharmacy course required students to play the MedSMA℞T game for up to 30 minutes and participate in group discussions about their experience playing the game. 26 Student pharmacists held positive outlooks of the game’s graphics, appearance, and storylines. Students suggested that there was some difficulty in identifying level objectives, but the complexity of the game was appreciated, nonetheless.…”
Section: Iterative Refinement and Implementationmentioning
confidence: 99%
“…In some simulations, students did report increased confidence in their abilities [ 15 ]. Additional technology-enhanced games focused on creating player avatars that participants could utilize to interact with game elements to practice certain skills and advance or level up [ 17 , 18 ]. These simulations focused more on the enjoyment and experience of the user as opposed to evaluating impact on formal student outcomes [ 17 , 18 ].…”
Section: Design Of Games In Pharmacy Educationmentioning
confidence: 99%